2013
DOI: 10.1128/jvi.03549-12
|View full text |Cite
|
Sign up to set email alerts
|

Full Conversion of the Hemagglutinin-Neuraminidase Specificity of the Parainfluenza Virus 5 Fusion Protein by Replacement of 21 Amino Acids in Its Head Region with Those of the Simian Virus 41 Fusion Protein

Abstract: dFor most parainfluenza viruses, a virus type-specific interaction between the hemagglutinin-neuraminidase (HN) and fusion (F) proteins is a prerequisite for mediating virus-cell fusion and cell-cell fusion. The molecular basis of this functional interaction is still obscure partly because it is unknown which region of the F protein is responsible for the physical interaction with the HN protein. Our previous cell-cell fusion assay using the chimeric F proteins of parainfluenza virus 5 (PIV5) and simian virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…In a recent study, using a homology model of the measles virus F protein based on the atomic structure of the prefusion PIV5 F protein (15), residues near the base of the measles virus F model were postulated to be involved in the H interaction (49). Certain measles virus F mutant proteins that were expressed on the surfaces of cells lost the ability to coimmunoprecipitate H protein and were unable to promote fusion, supporting the notion that the mutations were in a region of F that interacts with H. Also, in a separate study, regions of specificity of F proteins involved in HN interaction were identified based on chimeric proteins generated between PIV5 F and simian virus 41 (SV41) F proteins (50,51).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In a recent study, using a homology model of the measles virus F protein based on the atomic structure of the prefusion PIV5 F protein (15), residues near the base of the measles virus F model were postulated to be involved in the H interaction (49). Certain measles virus F mutant proteins that were expressed on the surfaces of cells lost the ability to coimmunoprecipitate H protein and were unable to promote fusion, supporting the notion that the mutations were in a region of F that interacts with H. Also, in a separate study, regions of specificity of F proteins involved in HN interaction were identified based on chimeric proteins generated between PIV5 F and simian virus 41 (SV41) F proteins (50,51).…”
mentioning
confidence: 64%
“…Other residues postulated to disrupt measles F-H interactions were located along the base of the measles virus F head model in domain I. Also, in a separate study, switching domain I fragments of PIV5 F with those of SV41 F converted the HN specificity of PIV5 F, resulting in partial triggering of this PIV5-SV41 chimeric F protein by the SV41 HN protein (51). Thus, to probe further the role of domain I of the PIV5 F prefusion structure in HN interaction and fusion promotion, mutations were generated within domain I, near the region of interaction between two protomers.…”
Section: Design Of Single Point Mutations In the Parainfluenza Virus mentioning
confidence: 99%
“…It is important in this context to note that the HN protein specificity of the F protein also is not solely defined by the primary structure of the F head domain, as we have reported previously (21,31).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found that a chimeric PIV5 F protein, no. 36, whose 21 amino acids in the head domain are replaced with the SV41 F counterparts, is triggered by the SV41 HN protein but not by the PIV5 HN protein (21). On the other hand, we previously created an SV41 F-specific chimeric HPIV2 HN protein, CH95-571, whose N-terminal 94 residues including the FAR were replaced with the SV41 HN counterparts (10); CH95-571 was renamed SCA for convenience sake in the current study ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation